RUANG LINGKUP KAJIAN AYAT – AYAT AKHLAK DALAM ILMU TAFSIR: ANALISIS METODOLOGIS - Dimas Taufiqurahman; Rangga Saputra; Imlan Dongoran (CV. Adiba Aisha Amira, 2025)
Interpretation of moral verses is a study that examines the understanding of verses in the Qur'an related to moral aspects, behaviour, and ethics in the lives of Muslims. This article aims to explore further the interpretation of moral verses and the scope of the study, including the methods of interpretation and their relevance in modern life. By reviewing previous studies on this topic, this article presents findings and discussions that outline various basic concepts of interpretation and their application to verses containing moral values in the lives of Muslims. This study discusses the interpretation of moral verses in the Qur'an and the scope of its study in the science of tafsir. Moral verses serve as a guide for humanity in living a life based on Islamic morality. This study employs a descriptive-analytical method, referencing various classical and modern tafsir works, such as Tafsir Al-Misbah, Tafsir Ibnu Katsir, and Tafsir Al-Munir. The research findings indicate that moral verses encompass aspects of human relations with Allah (habl min Allah), relations with fellow human beings (habl min al-nas), and relations with the environment. The scope of the study of the interpretation of moral verses also includes the methods of interpretation used, whether it be tafsir bi al-Ma'tsur, tafsir bi al-Ra'yi, or tafsir maqashidi.